2007
DOI: 10.1016/j.ejphar.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G protein signaling proteins differentially modulate signaling of μ and δ opioid receptors

Abstract: Effects of regulator of G protein signaling (RGS) proteins on μ and δ opioid receptors were investigated in HEK293 cells. Co-expression of RGS1, RGS2, RGS4, RGS9, RGS10 or RGS19 (Gα-interacting protein (GAIP)) significantly reduced [Tyr-D-Ala-Gly-N-methyl-Phe-Gly-ol]-Enkephalin (DAMGO)-induced inhibition of adenylyl cyclase (AC) mediated by μ opioid receptor, but only RGS9 decreased the effects of [Tyr-D-Pen-Gly-p-Chloro-Phe-D-Pen]-Enkephalin (DPDPE) mediated by δ opioid receptor. When C-tails of the receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Cells were grown in DMEM supplemented with fetal bovine serum (10%), penicillin (100 U/ml), streptomycin (100 g/ml), and nonessential amino acids (0.1 mM) at 5% CO 2 and 37°C, and G-418 (Geneticin) was used for selection or maintenance of selection of stable cell lines. Calcium phosphate transfection was performed as described elsewhere (Xie et al, 2005(Xie et al, , 2007a to introduce the receptor and/or transporter into different cells for assays. For cotransfection, the ratio of constructs and the amount of total DNA were held constant with pcDNA3.1.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown in DMEM supplemented with fetal bovine serum (10%), penicillin (100 U/ml), streptomycin (100 g/ml), and nonessential amino acids (0.1 mM) at 5% CO 2 and 37°C, and G-418 (Geneticin) was used for selection or maintenance of selection of stable cell lines. Calcium phosphate transfection was performed as described elsewhere (Xie et al, 2005(Xie et al, , 2007a to introduce the receptor and/or transporter into different cells for assays. For cotransfection, the ratio of constructs and the amount of total DNA were held constant with pcDNA3.1.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown in DMEM supplemented with fetal bovine serum (10%), penicillin (100 U/ml), streptomycin (100 g/ml), and nonessential amino acids (0.1 mM) at 5% CO 2 and 37°C, and G418 was used for selection or maintenance of selection of stable cell lines. Calcium phosphate transfection was performed as described elsewhere (Xie et al, 2005(Xie et al, , 2007a to introduce the necessary receptor and transporter into different cells for assays. For cotransfection, the ratio of constructs and the amount of total DNA was held constant with pcDNA3.1.…”
Section: Methodsmentioning
confidence: 99%
“…For example, as noted already, endogenous RGS4 does not act as a GAP for endogenous MOR signaling in SH-SY5Y cells (Wang et al, 2009) and the RGS4 knockout mouse shows only very minor phenotypic responses to morphine (Grillet et al, 2005;Han et al, 2010). On the other hand, RGS4 has been reported to act negatively to modulate MOR signaling in various heterologous systems (Ippolito et al, 2002;Garnier et al, 2003;Xie et al, 2005;Georgoussi et al, 2006;Xie et al, 2007;Talbot et al, 2010). NOPR couples to Gai/o proteins and so is expected to be sensitive to the GAP activity of RGS proteins (Xie et al, 2005).…”
Section: Rgs19 Modulates M-opioid Receptor Signalingmentioning
confidence: 99%
“…Thus, the apparent selectivity of RGS19 as a GAP for MOR signaling and RGS4 as a GAP for DOR signaling is unexpected. However, there is accumulating evidence for GPCRs contributing to the specificity of RGS protein action (Xu et al, 1999;Saitoh et al, 2002;Wang et al, 2002Wang et al, , 2009Bernstein et al, 2004), and we (Wang et al, 2009) and others (Georgoussi et al, 2006;Xie et al, 2007) have suggested a role for the C-terminus of opioid receptors in providing specificity of RGS action at DOR versus MOR. Moroever, outside the RH domain, RGS19 has a more complex structure than RGS4 with an N-terminal cysteine string that binds to the N-terminal leucine-rich region of GAIP-interacting protein N-terminus (Fischer et al, Fig.…”
Section: Rgs19 Modulates M-opioid Receptor Signalingmentioning
confidence: 99%
See 1 more Smart Citation